2009
DOI: 10.1021/bc900130f
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation Promotes Hemoglobin Tetramer Dissociation

Abstract: Hemoglobin conjugated with poly(ethylene glycol) (PEG) acts as an oxygen carrier free in plasma, substituting red blood cells in supplementing oxygen in hypo-oxygenation pathologies. Given the complexity of oxygen delivery controls, subtle structural and functional differences in PEGylated hemoglobins might be associated with distinct physiological responses and, potentially, adverse effects. We have compared hemoglobin PEGylated under anaerobic conditions, called PEG-Hb(deoxy), with hemoglobin PEGylated under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 65 publications
(98 reference statements)
3
51
1
Order By: Relevance
“…tetramers containing 4 unmodified protein subunits) (Table I). The calculation was carried out by means of a combinatorial procedure that we previously reported for PEGylated hemoglobin (42). The results show that i) Dr Uox PEGylation with MAL-PEG of different molecular weight resulted in similar PEGylation yields, and ii) despite the relative abundance of non-PEGylated monomers, after quaternary assembly only a low percentage of unmodified tetramers occurs (Table I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tetramers containing 4 unmodified protein subunits) (Table I). The calculation was carried out by means of a combinatorial procedure that we previously reported for PEGylated hemoglobin (42). The results show that i) Dr Uox PEGylation with MAL-PEG of different molecular weight resulted in similar PEGylation yields, and ii) despite the relative abundance of non-PEGylated monomers, after quaternary assembly only a low percentage of unmodified tetramers occurs (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…In order to change the target aminoacid for the PEGylation reaction, while using the same PEG derivative (MAL-PEG), we took advantage of the extension arm-facilitated PEGylation, a two-step procedure which has already been used in PEGylation of human hemoglobin to increase the number of reaction sites (33,44) while avoiding the derivatization of cysteines with crucial role in protein activity (42,45). Dr Urad was pretreated with 2-iminothiolane (IMT), a cyclic molecule that reacts with the primary amino groups of lysine and N-terminal residues to form sulfhydryl groups.…”
Section: Resultsmentioning
confidence: 99%
“…The present conflict between the molecular masses of the PEG-modified enzymes estimated from SDS-PAGE analysis and their individual molecular masses seems to be consistent with the previous results on the SDS-PAGE and MALDI-TOF MS analyses of the PEGmodified proteins. [21,22] They demonstrated that the apparent molecular weights of the PEG-modified proteins on SDS-PAGE were higher than their actual molecular weights on MALDI-TOF MS. Therefore, taking the present and previous findings into consideration, it was concluded that the PEG-modified PAA hydrolases-1 made their molecular weights seem higher on SDS-PAGE than the actual ones and possibly contained 1-5 PEGs per molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The tetramer dimer-tetramer dissociation constant of these PEGylated molecules with Cys-93(b) free is indistinguishable from that of unmodified Hb; the presence of PEGylation on Cys-93(b) has only very small influence on the dissociation constant. On the other hand, a comparison of the stability of quaternary structure of MP4 versus Euro PEG Hb has suggested that in MP4 the quaternary structure of the molecule (Caccia et al 2009) has been weakened leading to the presence of dissociated PEGylated species. This may be the influence of one-step versus two-step EAF PEGylation platform.…”
Section: Hemospan and Euro-peg Hbmentioning
confidence: 99%